Understanding the Puzzle Behind the Pictures - Amy Price Azano; Mary Tackett; Miranda Sigmon (SAGE Publishing, 2017)
The growing visibility of autism spectrum disorder (ASD) and the trend toward inclusive classroom practices present teachers with the unique responsibility of providing an inclusive learning environment for all students. This study sought to explore how teachers may use children's picture books about autism to provide nondisabled students with experiences aimed at increasing student understandings toward autism. Researchers compiled 35 children's books for content analysis and identified significant themes presented as five assertions. Findings indicate children's picture books about autism may (a) teach readers about the core characteristics of ASD, (b) illustrate how individuals with autism may be "at risk," (c) expand on ways neurotypical children are similar and different to individuals with autism, (d) emphasize the importance of influential language, and (e) present insights about autism through the use of multiple perspectives. Findings with exemplar texts representative of each theme are presented, and practical classroom applications are discussed.